PREVALENCE OF THERAPEUTIC INERTIA AND ITS ASSOCIATED FACTORS AMONG PATIENTS ON BRONCHIAL ASTHMA MANAGEMENT IN A REFERRAL TEACHING HOSPITAL IN SOUTHWEST ETHIOPIA, 2023: A CROSS-SECTIONAL STUDY. - Lake, Getinet; Yoo, Samuel Deok Jong; Gashahun Mekonnen Disasa,; Tenaye Abate Temesgen, (Student's Journal of Health Research Africa, 2023)
Background: Therapeutic inertia may be one of the factors responsible for inadequate asthma control. However, the magnitude of therapeutic inertia in asthmatic patients has not yet been determined. In Ethiopia, a result showed that more than half of people with asthma had uncontrolled asthma. Objectives: to assess the prevalence of therapeutic inertia and its determinant factors among patients on bronchial Asthma management. Methodology: An institution-based cross-sectional study was conducted on adult asthmatic patients attending the chronic follow-up department at Jimma University Medical College. A consecutive sampling with an interviewer-administered questionnaire and patient chart review was performed. Results: Therapeutic inertia was identified in 63 (47.7%) study subjects. The associated factors among patients on bronchial asthma management were poor adherence to medications prescribed by a doctor (p-value= 0.013; AOR 5.9; 95% CI 1.5-23.9), no regular follow-up (p-value=0.010; AOR 9.766; 95% CI 1.727-55.216), mild persistent chronic asthma (p-value <0.001; AOR 0.003; 95% CI 0.001-0.069) and poor provision of verbal explanation about asthma medication (p-value <0.001; AOR 0.113; 95% CI 0.049-0.261). Conclusion: The prevalence of therapeutic inertia among the study population was high. In the majority of cases with therapeutic inertia, asthma treatment necessitates treatment de-escalation and a step-up intervention. This is more likely to happen to patients with poor compliance and no regular follow-up. Mild persistent asthma and verbal explanations of medication dosage reduce the risk. Recommendations: The growing incidence of therapeutic inertia in asthma management calls for severity-based treatment plans, standard care, education on quitting smoking, appropriate medication counseling, and frequent follow-up visits. In 21% of patients with severe chronic asthma, uncontrolled cases may necessitate additional treatment alternatives.